WANITA “AHMADI” DALAM NOVEL MARYAM: KAJIAN PSIKOLOGI B.F. SKINNER - Muhammad Hambali; Saharudin Saharudin; Muh. Khairussibyan (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
This study aims to examine the psychology of the main character in the novel Maryam by Okky Madasari in order to determine the response stimulus experienced by the main character and other characters with the literary psychology approach of B.F. Skinner. The data source of this research is the novel Maryam by Okky Madasari. The results showed that the psychology of Maryam's character as a woman "Ahmadi" was closely related to the stimulus response she experienced. The response stimuli include; (1) operant conditioning, found 5 conditioning data, one of which was through the stimulus given by her family, (2) formation, found 8 shaping data, where it is said that the characters Fatimah, Jamil and Zulkhair helped shape Maryam, (3) reinforcement , found data with a total of 7 reinforcers including primary and secondary reinforcement, primary reinforcer responded by Mrs. Maryam and secondary reinforcer when Maryam helped Zulkhair, (4) generalization, found 6 generalization data, where the stimulus from Mr. and Mrs. Zul was then generalized by the character Maryam and (5) avertive stimulus, found 5 avertive stimulus data, one of which was when Maryam's character violated the rules given by her parents. Thus, the psychology of Maryam's character is formed or patterned through these five stages and the most influential in shaping Maryam's "Ahmadi" figure is the stimulus response from Maryam's character and other characters.